Wewnętrzne i zewnętrzne uwarunkowania poziomu bezrobocia w Polsce do 2010 r. - Hybel, Jan (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2001)
The paper deals with some internal and external factors that are likely to influence labour market in Poland till 2010. An analysis was focused on the relationship between the unemployment level and the following factors: economic growth rate, demographic changes and foreign trade balance. Moreover, the - unemployment in Poland and in the European Union's countries as well as methods of its reduction have been presented. The Author concludes that faster economic growth, even up to 5%, will not contribute to unemployment decline in Poland. In fact, the high unemployment in our country results from the demographic boom, the economy restructuring, high labour costs, low profitability in the sector of SME as well as from slowing tendency in growth of export sales.